2019
DOI: 10.1111/his.13811
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemoradiation for patients with advanced oesophageal cancer – which response grading system best impacts prognostic discrimination?

Abstract: Aims Neoadjuvant chemoradiation reduces tumour volume and improves the R0 resection rate, followed by extended survival for patients with advanced oesophageal cancer. The degree of tumour regression has high prognostic relevance. To date, there is still no generally accepted tumour regression grading system. The aim of this study was to compare the prognostic discrimination power of different histological regression grading systems: (i) the fibrosis/tumour ratio within the primary tumour (Mandard classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…For the Mandard TRG, some studies supported that TRG 1-2 should be classified into responders, which was in accordance with our study [7,18,19], while some others believed that TRG 1-3 was better in distinguishing the prognosis [20][21][22]. For the Becker TRG, there were studies supporting the same consequence as ours [1,[23][24][25], while others suggested TRG 1-2 owned a better prognosis than TRG 3 [9,10,26,27]. This discrepancy might partly derive from the differences in subjective evaluations of the pathologists.…”
Section: Discussionsupporting
confidence: 89%
“…For the Mandard TRG, some studies supported that TRG 1-2 should be classified into responders, which was in accordance with our study [7,18,19], while some others believed that TRG 1-3 was better in distinguishing the prognosis [20][21][22]. For the Becker TRG, there were studies supporting the same consequence as ours [1,[23][24][25], while others suggested TRG 1-2 owned a better prognosis than TRG 3 [9,10,26,27]. This discrepancy might partly derive from the differences in subjective evaluations of the pathologists.…”
Section: Discussionsupporting
confidence: 89%
“…The mechanism leading to this phenomenon is likely the death of chemoradiation-sensitive cells in the basal layer of the cysts/furrows leading to exposure of luminal keratinous material which incites a strong histiocytic and giant cell response. Tumor regression in the esophagectomy specimen in patients who receive neoadjuvant chemoradiation is prognostic [9]. Tumor regression in carcinoma cuniculatum is difficult to assess as distinguishing dyskeratotic/apoptotic cells from terminally differentiated but viable cells is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Except for the status of lymph node, other pathological factors including T stage [ 8 , 22 , 23 ], the Lauren classification [ 22 , 27 ], the grade of differentiation [ 11 , 22 ], and tumor type [ 28 , 29 ] were also considered to correlate with TRG, which might affect the significance of this system. More studies are needed to investigate if the TRG system would show different significance on prognosis in patients with various clinicopathological characteristics.…”
Section: Discussionmentioning
confidence: 99%